Executive and Organizational Coaching: A Review of Insights Drawn From Literature to Inform HRD Practice. (May 2014) - Maltbia, Terrence E.; Marsick, Victoria J.; Ghosh, Rajashi
The Problem: Differing perceptions of what constitutes executive coaching core competencies by academic and coach preparation programs, credentialing associations, and practitioners obfuscates clarity of definition, roles, and implementation. This lack of clarity and agreement can confuse practitioners and slow progress in theory-building, research, and executive coach development. The Solution: This article examines diverse ways that executive coaching is defined and distinguished. Professional associations have shaped membership, credentialing, and accreditation based on different competencies. The article describes four executive coaching roles and six enabling core coaching competencies, and it draws implications for navigating, researching, and practicing in the diverse terrain of executive coaching, in and for, organizations. The Stakeholders: Practitioners might be interested in a map of the coaching terrain that Enables them to better choose among possible avenues toward coach preparation and professionalization. Researchers and theory builders might be interested in definitions and competency models to guide further investigation into coaching.